PEMBERIAN PUPUK BOKASHI DAN URINE SAPI PADA PEMBIBITAN TANAMAN KAKAO (Theobroma cacao L.) - Irawan, Adi Candra; Khoiri, M. Amrul; ', Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
This research aims to determine the effect of the interaction of Bokashi fertilizer and cow urine as well as to get the best treatment on the growth of the cocoa plant. The research was conducted in August until November 2014 at the experimental garden of Agriculture, University of Riau, Bina Widya road 12.5 km Simpang Baru , Tampan, Pekanbaru.      This research was conducted using a completely randomized design (CRD) with two factors and three repetition. The first factor is bokashi (B) consisting of 4 levels,                    were: 0 g / polybag (B0), 50 g / polybag (B1), 75 g / polybag (B2), 100 g / polybag (B3) and the second factor is Urine (U) which Consist 4 levels, were: 0 ml / L of water (U0), 300 ml / L of water (U1), 400 ml / L of water (U2) and 500 ml / L of water (U3). Parameters measured were: seedling height, number of leaves, leaf area, stem circumference, seedling dry weight, and root crown ratio. Research results show that the interaction of Bokashi fertilizer and cow urine with the dose of 75 g / polybag and        400 ml / L of water, is the best dose to increase seedling height, leaf area, dry weight and root crown ratio. Bokashi fertilizer with 75 g / polybag is the best dose for increasing seedling height, number of leaves, leaf area, girth and dry weight. Cow urine application at the dose of 400 ml / L of water is the best dose for enhancing seedling height, leaf area and dry weight.   keyword: Cacao seedling, bokashi fertilizer, cow urine